Literary genre, medieval studies, and the prosthesis of disability. Issue 7 (9th November 2016) - Orlemanski, Julie
ABSTRACT: Because 'disability' is a concept anachronistic to the Middle Ages, the subfield of medieval disability studies calls for complex negotiations of temporality and historicist interpretation. This essay regards medieval disability as a historicist 'prosthesis' and seeks to clarify what new capacities, altered interpretations, and critical insights it yields. What happens, I ask, when disability's untimely prosthesis does not fit ? The prominent medieval genre of the exemplum, or brief illustrative tale, provides my case study. Full of stereotyped and instrumental representations of impairment, exemplary stories seem to jar against the values of disability studies - but is their significance only negative? I argue that studying disability in medieval literature calls for reading with tendentious solidarity, I and show what this might look like by interpreting one of the tales of the Gesta Romanorum . Ultimately I claim that wilful and prostheticised reading practices are not deviant from the history of textual meaning, but central to it.